2018
DOI: 10.18494/sam.2018.1955
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-sensitivity Graphene-based Strain Gauge Sensor: Fabrication on Si/SiO2 and First-principles Simulation

Abstract: Monolayer and multilayer graphene films have been grown on a Cu substrate by chemical vapor deposition (CVD) and then transferred onto a SiO 2 /Si substrate using polymethyl methacrylate (PMMA) to fabricate an ultrasensitive graphene-based strain gauge sensor. The graphene films were patterned using a CO 2 laser beam. The sensitivity and temperature dependence of the gauge factor (GF) of the fabricated sensors were examined at different applied strains and operating temperatures up to 0.05% and 75 °C, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The sensor exhibited not only excellent response and reversibility behavior as a function of deflection, but also good repeatability and acceptable linearity. A highly sensitive strain gauge based on graphene piezoresistivity was presented by Gamil et al 47 The fabricated gauges based on monolayer and multilayer graphene films showed a stable GF of 255 and 104 within the applied temperature range, respectively (Figure 6(c) and (d)). CB-based film strain sensor.…”
Section: Performance and Mechanism Of Carbon-based Film Strain Sensorsmentioning
confidence: 95%
See 4 more Smart Citations
“…The sensor exhibited not only excellent response and reversibility behavior as a function of deflection, but also good repeatability and acceptable linearity. A highly sensitive strain gauge based on graphene piezoresistivity was presented by Gamil et al 47 The fabricated gauges based on monolayer and multilayer graphene films showed a stable GF of 255 and 104 within the applied temperature range, respectively (Figure 6(c) and (d)). CB-based film strain sensor.…”
Section: Performance and Mechanism Of Carbon-based Film Strain Sensorsmentioning
confidence: 95%
“…Key steps in fabricating the single-walled carbon nanotube (SWCNT) strain sensor. 36 gauge based on graphene piezoresistivity was presented by Gamil et al 47 Monolayer and multilayer graphene films have been grown on a copper (Cu) substrate by CVD and then transferred onto a silicon dioxide/silica (SiO 2 /Si) substrate using polymethyl methacrylate to fabricate it (Figure 3(c)).…”
Section: Fabrication Of Carbon-based Film Strain Sensorsmentioning
confidence: 99%
See 3 more Smart Citations